EFESIENSI DAN EFEKTIFITAS SISTEM APLIKASI PENGELOLAHAN ASSET INVENTARIS MENGGUNAKAN METODE AHP PADA KANTOR KUD SUMBER PANCA USAHA PANDAAN - M. Noval Riswandha; Rahadi Nur Firmansyah (SPIRIT, 2017)
In the Inventory Asset Management Application Using Visual Basic.10.Net office will support the efficiency and effectiveness of work in data processing to obtain the required information. The purpose of writing this final project to analyze, design and implement the Asset Inventory Management Applications In offices. Using Visual Basic.10.Net. The software developed in the preparation of this final project using Microsoft Visual Basic 10.Net with phpmyadmin mysql database that allows displaying the information in text form and the graphs. The end result of this research is produced Asset Inventory Management Application program that can provide a clear overview of the Asset Inventory Management Applications In Office Using Visual Basic 10.NetKeywords: Vb.net 2010, Mysql, Decision Support System.